2018
DOI: 10.1186/s12711-018-0383-0
|View full text |Cite
|
Sign up to set email alerts
|

Eigen decomposition expedites longitudinal genome-wide association studies for milk production traits in Chinese Holstein

Abstract: BackgroundPseudo-phenotypes, such as 305-day yields, estimated breeding values or deregressed proofs, are usually used as response variables for genome-wide association studies (GWAS) of milk production traits in dairy cattle. Computational inefficiency challenges the direct use of test-day records for longitudinal GWAS with large datasets.ResultsWe propose a rapid longitudinal GWAS method that is based on a random regression model. Our method uses Eigen decomposition of the phenotypic covariance matrix to rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Additionally, DRP obtained from the routine national genetic evaluation of millions of individuals, instead of EBV, were used as the response variable, which benefited from correcting confounding environmental factors and taking advantage of population pedigree information. Our results were similar to the outcome of Ning et al (2018b), who validated their novel longitudinal GWAS method using test-day records with the same chip data and conducted a GWAS of MY, FP, and PP in the first 3 parities.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Additionally, DRP obtained from the routine national genetic evaluation of millions of individuals, instead of EBV, were used as the response variable, which benefited from correcting confounding environmental factors and taking advantage of population pedigree information. Our results were similar to the outcome of Ning et al (2018b), who validated their novel longitudinal GWAS method using test-day records with the same chip data and conducted a GWAS of MY, FP, and PP in the first 3 parities.…”
supporting
confidence: 78%
“…In our study, a Chinese Holstein population of 6,675 cows were genotyped with the BovineSNP50v1 Bead-Chip (54,001 SNP; Illumina Inc.), the BovineSNP50v2 BeadChip (54,609 SNP; Illumina Inc.), and the Gene-Seek Genomic Profiler HD (76,879 SNP; Neogen Corp., Lansing, MI), which were described in our previous longitudinal GWAS (Ning et al, 2018b). The individuals genotyped with the GeneSeek Genomic Profiler HD chip were used as reference, and all others were imputed to the high density of 70k SNP by using FImputev2.2 (Sargolzaei et al, 2014).…”
mentioning
confidence: 99%
“…The accumulated 305‐day milk yield is estimated by summing the test‐day milk yield (TDMY) recorded every day during the lactation period or combining the weekly or monthly TDMY by linear interpolation (Schaeffer, ). Since the additive genetic variance for milk yield changes during lactation (Bignardi, El Faro, Cardoso, Machado, & de Albuquerque, ; Singh et al, ), the genetic effects of QTL related to 305‐day milk yield are not constant during the lactation period; therefore, many QTL whose genetic effects change during lactation might not be detected in this approach (Lund, Sorensen, Madsen, & Jaffrézic, ; Ning et al, ). Strucken, Bortfeldt, De Koning, and Brockmann () showed that lactation curve parameters provide a higher power to screen the whole genome for region whose effect change during lactation.…”
Section: Introductionmentioning
confidence: 99%
“…However, their method was shown to be computationally inefficient due to the high dimensionality of the mixed model equations compared to other models. Subsequently, Ning et al (2018) proposed a rapid longitudinal GWAS method, transforming the covariance matrices to diagonal matrices using eigen-decomposition. This way the model can be solved by a weighted least squares model for each SNP test.…”
Section: Detecting Qtl and Causal Variants Associated With Longitudinal Traitsmentioning
confidence: 99%